Pengaruh Budaya Organisasi, Aktualisasi Diri, dan Penghargaan terhadap Prestasi Kerja Karyawan PT. Kereta Api Indonesia (Persero) DAOP IV Semarang - Ani Desriana; Handoyo Djoko Waluyo; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2015)
This study aimed to describe the influence of organizational culture, self-actualization, and esteem to employee performance of PT. Kereta Api Indonesia (Persero) DAOP IV Semarang. The sample method is census of the entire population of 110 respondents was sampled. The author used SPSS 16.0 program to test the regression on the data analysis. The result it can be concluded partially that the variabels has positive influence and significant to employee performance. Organizational culture on the employee performance by during t test (5,772) > t table (1,659). Self-actualization on the employee performance by during t test (5,772) > t table (1,659), and esteem on the employee performance by during t test (7,325) > t table (1,659). Simultaneously, these variabels have a positive influence and significant on the employee performance with the result of F-test (27,262) > F-table (2,690). To improve employee performance, PT. Kereta Api Indonesia (Persero) DAOP IV Semarang shall be improving the innovating potency of employee, open up opportunities for employee to take education and training, and increasing rewards.